2013
DOI: 10.1093/bjsw/bct164
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Children Reported to the Child Protection Department in Western Australia

Abstract: This study of management information provides data on all reports, investigations and findings of maltreatment of children in Western Australia from their birth in 1990 or 1991 until their eighteenth birthday. It provides prevalence rates of children being reported, investigated and found to have been maltreated. A study of more recent cohorts shows trends in recent years. A key finding is that over 13% of all children born in 1990 and 1991 were reported before reaching the age of eighteen although 71% of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…A growing body of research across what have become known as Anglophone countries with similar systems (Lonne et al, 2009) suggests that there has been a considerable increase in the numbers of families experiencing investigations for suspected abuse in the last decades (Bilson et al, 2015, Devine and Parker, 2015, Trocme et al, 2014. Further interrogation suggests that the vast majority of such investigations do not uncover actual abuse and/or result in help being offered to families (Trocme et al, 2014).…”
Section: Are We Looking In the Right Places Or At The Right Issues?mentioning
confidence: 99%
“…A growing body of research across what have become known as Anglophone countries with similar systems (Lonne et al, 2009) suggests that there has been a considerable increase in the numbers of families experiencing investigations for suspected abuse in the last decades (Bilson et al, 2015, Devine and Parker, 2015, Trocme et al, 2014. Further interrogation suggests that the vast majority of such investigations do not uncover actual abuse and/or result in help being offered to families (Trocme et al, 2014).…”
Section: Are We Looking In the Right Places Or At The Right Issues?mentioning
confidence: 99%
“…This increasing trend, in which over 60% of investigations do not find that children are suffering or likely to suffer significant harm, is increasing the stress on and causing harm to a growing number of families and simultaneously reducing the likelihood that these children receive help. This trend of an increasing involvement of children in the child protection system is seen in a number of countries (Bilson et al, 2015;Munro and Manful, 2012) where the broadening of criteria from maltreatment to responding to children's well-being leads to more investigations (e.g. Trocmé et al, 2014;Bilson et al, 2016) and children entering state care (Gilbert et al, 2011;Bilson et al, 2016).…”
Section: Child Protection Processmentioning
confidence: 99%
“…Across Australia statistics from client information systems and longitudinal studies have shown referral rates to the child protection system before the age of 18 to be around 1 in 4 children in New South Wales, Queensland and Victoria (Scott, 2014 p. 16) with the lowest published ratio being 1 in 8 in (Bilson et al, 2015). A study undertaken in California (Magruder and Shaw, 2008, p. 178 ) found that 19.8% of children were reported before the age of 7.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…) and, in Australia, about rates of intervention and outcomes for children from the majority and indigenous populations (Bilson et al . ). In Britain, too, racial ‘disproportionality’ has been the focus of some attention.…”
Section: Introductionmentioning
confidence: 97%
“…Child welfare systems internationally exhibit very large inequalities in a variety of respects (Bilson et al . ; Bywaters ; Bywaters et al . ; Eckenrode et al .…”
Section: Introductionmentioning
confidence: 99%